Proposed new interior design of Perpustakaan Cawangan Kajang for Perbadanan Perpustakaan Awam Selangor at 2, Jalan Metro Avenue 2, 43000 Kajang, Selangor Darul Ehsan / Nur Arija Abdullah - Abdullah, Nur Arija (Faculty of Architecture, Planning and Surveying, 2011)
The final project for the final year students in Interior Architecture is based on all knowledge gained from all the past semesters. All the knowledge will be put to the testing proposing a final project based on real life factors such as the project itself, the client, the site, and the budget. The project chosen must have its own general and design issue related for it to be a visible project. This report is about proposing a new design scheme of Perpustakaan Cawangan Kajang for Perbadanan Perpustakaan Awam Selangor (PPAS) at 2, Jalan Metro Avenue, Metro Avenue, 43000 Kajang, Selangor. At the moment, Perpustakaan Cawangan Kajang is situated at second floor of Bangunan Dato’ Nazir which is the main attraction the Kajang town because Haji Sahmuri’s Satay Restaurant is located right under the library. Unfortunately, disabled cannot access the library as it is situated on the second floor and there is no elevator or any facilities that can bring them to enter the library. There is also a statement made by the library administration and Majlis Pertandaran Kajang (MPKj) to move the library to a new building or shop lot which issued in local newspaper, Sinar Harian dated 29th April 2009. Until now, the library does not change places as PPAS headquarter itself is planning to move and they are running out of budget to make any other library’s improvement for the time being. The concept that was chosen for this project is ‘Flipping through pages’ which means revealing the content in the roughly stage. The image that will be applied in the design is contemporary and a slight of ‘green-design’ on its architecture to meet the current green-building requirement.